Passio Animi: Desire, Will and Servitude - The concept of Leidenschaft in Kantian Anthropology - - Carvalho, Vasco S. (Con-Textos Kantianos. International Journal of Philosophy, 2024)
The present study deals with the kantian concept of Leidenschaft, i.e., Passion. We aim to determine its meaning, in the context of Kant's thought. To accomplish this, we introduce and explain all its antecedent concepts. Thus, this study corresponds to a sequential analysis of a set of kantian concepts (i.e., Desire, Sensitive Desire, Inclination, Passion) and the relationship that is established between them. We conclude that Passion is a species of Desire, fundamentally distinguished from every other desire by the intensity and ascendancy of its desiderative pressure, and by the parallel – and peculiar – state of Servitude in which it secludes its subject.